Satisfaction of the Fisheries Troll Line Service Section of the Port Authority at Bungus PPS, West Sumatra - Oktakasia, Yopy; Zain, Jonny; Bustari, Bustari (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
The purpose of this research is to improve and revise the service quality performance that is given to fishermen. The method used in this research is to use a survey method with direct interviews using questionnaires at the research location. Respondents in this research were addressed to Troll Line Fishermen. The analysis used is the validity and reliability test obtained from the questionnaire results, the Customer Satisfaction Index (CSI) is used to determine the level of satisfaction of fishermen and Importance and Performance Analysis (IPA) is used to find out the things that are priority improvements to the attributes that affect consumer satisfaction level. Based on the Customer Satisfaction Index (CSI) method, the results obtained 95.082%, which indicates that the level of service provided by the porter’s party where it can be seen that the service users have a high level of satisfaction with the harbormaster's service